The Effect of Product Packaging Innovation, Branding, and Technological Capability on MSME Performance: A Case Study of Fresh Noodle Producers in The Madiun Residency - Purnomo, Rochmat Aldy; Sartika, Rebecca Cindy; Juwita, Aulia Hapsari; Chamidah, Siti; Hartono, Sri; Nguyen, Thi Thom Thom (School of Business, IPB University (SB-IPB), 2025)
Background: The COVID-19 pandemic has significantly impacted the Indonesian economy, highlighting the crucial role of Micro, Small, and Medium Enterprises (MSMEs) in economic recovery. While previous studies have explored general MSME performance, there is a lack of focused research on how innovative strategies in product packaging and branding can directly impact the operational success of fresh noodle producers.Purpose: This study aims to fill existing research gaps by addressing the limited empirical data on the specific factors influencing the performance of MSMEs in the food production sector, particularly in the context of fresh noodles.Design/Methodology/Approach: An explanatory quantitative approach was used to explore the relationships between these variables. A sample of 40 respondents was selected using purposive sampling, with the criteria that respondents must be fresh noodle producers, located in the Madiun residency area, and have been in business for at least 2 years. Data analysis was performed using multiple regression analysis with SPSS 25 software to examine the cause-and-effect relationships between product packaging innovation, branding, technological capability, and MSME performance.Findings/Result: The results indicate that product packaging innovation, branding, and technological capability have a significant positive impact on the performance of fresh noodle MSMEs. Simultaneously, all three variables significantly contribute to the overall performance of MSMEs in the Madiun Residency.Conclusion: This study offers practical guidance for entrepreneurs and stakeholders in designing strategies to support MSME sector growth. It provides actionable insights into how fresh noodle producers can improve their market presence and overall performance.Originality/Value (State of the Art): By concentrating on innovative strategies in product packaging and branding specifically for fresh noodle producers, this study provides a unique contribution to the broader understanding of MSME dynamics in Indonesia, particularly within the food production sector. Keywords: product packing innovation, branding, technological capability, MSME performance, multiple regression